PUBERTY NEUROENDOCRINOLOGY AND GONADOTROPIN RELEASING HORMONE NEURONS - Yardimci, Ahmet; Kelestimur, Haluk (Nobel Ilac, 2019)
Gonadotropin releasing hormone (GnRH) is a hormone that plays a key role in the development of puberty and is secrete from various neuronal groups in the hypothalamus. GnRH neurons are called Pulse Generator since they secrete at regular intervals. Kisspeptin and its receptor KiSS1R are key factors in the control of GnRH secretion. GnRH secretion, which is stimulated by kisspeptin secretion, leads to the release of anterior pituitary reproductive hormones. luteinizing hormone (LH) and follicle stimulating hormone (FSH) These hormones, which are secreted from the anterior pituitary, ensure that gonads develop. perform their functions, and get mature Prior to puberty development, the GnRH pulse generator is suppressed in the interval of juvenile quiescence, and gonadotropin secretion is inhibited. Puberty occurs by the end of this inhibition. The frequency and amplitude of GnRH secretion increase by the development of puberty, and consequently, secretion of LH and FSH increases as well. As a result, secondary sex characters arise. Another important factor in puberty development is the hormone 'leptin'. Leptin levels are proportional to body energy reserve and the main function is to inform the brain about body's energy reserve and to prevent the development of obesity. In puberty development, hormone leptin plays a role as energy signal. The level of leptin increases before puberty, when energy reserves reach a sufficient level and puberty delays in its absence. In this review we discuss the relationship between puberty and GnRH neurons, the hormonal changes that occur before and after puberty development, and the possible mechanism that underlies puberty development.
Keywords: Puberty; GnRH; kisspeptin; LH; FSH